117k views
0 votes
Some help me with this please!!

Some help me with this please!!-example-1

1 Answer

6 votes

First of all observe that


r^6s^3=(r^2s)^3 \implies \sqrt[3]{r^6s^3}=\sqrt[3]{(r^2s)^3}=r^2s

So, we have


\log(r^5s^6\sqrt[3]{r^6s^3})=\log(r^5s^6\cdot r^2s)

We can simplify the input as


\log(r^5s^6\cdot r^2s)=\log(r^7s^7)

The logarithm of a multiplication is the sum of the logarithms:


\log(r^7s^7)=\log(r^7)+\log(s^7)

Finally, invoke the logarithm property
\log(a^b)=b\log(a)

to get the final answer


\log(r^7)+\log(s^7)=7\log(r)+7\log(s)

User CAustin
by
5.6k points